Development of Interactive Teaching Materials in Indonesian for Grade VI Elementary School Students - Widodo, Joko (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2022)
Interactive teaching materials are written materials in the form of sheets of paper that are bound and given covers and that present knowledge that is arranged systematically. This research aims to develop valid, effective, and practical teaching materials. This study uses a 4D research model with four stages: defining, designing, developing, and deploying. This teaching material has been validated by several experts, namely material experts, media design experts, and linguists. This study had three trials: individual trials, small group trials, and large group trials. Based on the combined percentage of validity of interactive teaching materials, according to experts, a percentage of 89% is categorized as